Temperature-constrained topology optimization of thermo-mechanical coupled problems. Issue 10 (3rd October 2019) - Zhu, Xuefeng; Zhao, Chao; Wang, Xuan; Zhou, Yu; Hu, Ping; Ma, Zheng-Dong
ABSTRACT: Temperature-constrained topology optimization for thermo-mechanical coupled problems under a design-dependent temperature field considering the thermal expansion effect remains an open problem. A temperature-constrained topology optimization method is proposed for thermo-mechanical coupled problems. In this article, the temperature values at the heat sources are constrained. The numerical results reveal that the temperature constraints play an important role in topology optimization of thermo-mechanical coupled problems. The optimized structure obtained by the presented method not only has certain strength but also decreases the temperature significantly compared with structures obtained by other methods without considering temperature constraints. The proposed method is applied to the design of the cooling system of a battery package. Numerical examples verify the efficiency of the presented method.